Bem-estar subjetivo e bem-estar no trabalho em profissionais de educação física - Valente, Luis Eduardo (2007)
Currently, well-being each time more gains space as important and integrant part of the life of the people. Research comes searching consequently to detach positive factors that exert influence in its personal life, and in its work. The objective of this study was to verify the relations between subjective well-being (composed for three dimensions: general satisfaction with the life, positive affection and negative affection) and well-being in the work (composed for three dimensions: satisfaction in the work, involvement with the work and affective organizational commitment) in professors of physical education who acted in schools and academies, describing the levels of subjective well-being and well-being in the work, analyses of variance and correlation between them. The sample was composed for 124 professors of physical education, 34 acted in private schools and 90 acted in academies, 81 of masculine sex and 43 of the feminine sex, single and married, with age between 21 and 59 years. The scholar knowledge was distributed since complete superior education until the concluded master degree. The instrument was a self-report questionnaire composed by five scales that had measured the variables of the study and a questionnaire of complementary data. The results had disclosed that swb and wbw keep relations between itself. The professors are considered relatively happy people with their personal life and had disclosed a medium relation with their professional life .the results of the correlations related to swb had signaled that the accumulation of negative experiences in their life could reduce deeply positive experiences and positive evaluations on their life and vice versa and to wbw in general demonstrated that satisfaction in the work, involvement with the work and affective organizational commitment are interdependent. As for the comparisons, for swb the professors who acted in academies had gotten significantly bigger averages of negative affection of what of schools and on the other hand, the average of general satisfaction with the life of the professors of schools was significantly superior to the one of that they acted in academies demonstrating that these had lived deeply more negative experiences of what the ones that worked in schools and that the school professors were more satisfied with its life of what of academies. For well-being in the work the general picture if keeps fellow creature for professors of physical education who acted in schools and academies, that is, the professors keep in the same intensity the bonds with the work that they execute and the organization employer. Future studies would have to increase the number of professors as well as, to investigate other areas of the physical education and compare them with the present study extending the studies involving well-being and professors of physical education.(AU)